THE EFFECTIVENESS OF LEARNING VIDEO USAGE TO SUPPORT ONLINE LEARNING IN BASIC CHEMISTRY COURSE DURING THE COVID-19 PANDEMIC - Meida Wulan Sari; Nurma Yunita Indriyanti; Bayu Antrakusuma; Budi Utami (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2021)
This study aims to determine the effectiveness of learning video usage to support online learning in basic chemistry course during the COVID-19 pandemic. The subjects in this study were 60 students from the 1st semester of the FKIP UNS Undergraduate Science Education Study Program who took basic chemistry course. This research was conducted in the odd semester of the 2020 or 2021 academic year. This research was conducted online and utilized the SPADA platform for viewing learning video. The data collection technique used a questionnaire. The use of questionnaires aims to obtain an overview of the effectiveness of learning video. Data analysis used quantitative descriptive with a score for each question, from 1 to 5. The results showed that the use of learning video during the COVID-19 pandemic could support online learning, namely obtaining an effectiveness percentage of 84% with a very good category. Therefore, learning video are effective in helping students understand the concepts that are being studied and motivating students to study online.